Insights into Clinical Features and Outcomes of Adrenal Cortical Carcinosarcoma - Zachery Branham; Ashley D. Fox; Asad Ullah; Nikhil G. Patel; Martha Terris; Jigarkumar Parikh (Diagnostics, 2022)
Adrenal cortical carcinosarcomas are a rare and typically aggressive malignancy with few reported cases in medical literature. We present a case of a 78-year-old female who presented with complaints of fatigue and right shoulder pain. Imaging of the abdomen with computed tomography visualized a large mass in the right upper quadrant. The mass was radiologically described as a 22 × 17 × 13 cm heterogeneous mass with its epicenter in the area of the right adrenal gland, with medial and peripheral effacement of all structures in the right upper quadrant. Non-contrasted images demonstrated anterior mid-portion calcifications. The mass parasitized its blood supply from several surrounding structures, including the liver and right psoas muscle, and extensively invaded the psoas muscle. Resection of the mass was performed with pathology, which revealed a high mitotic index and nuclear atypia with two morphologically and immunophenotypically distinct components. One of these components stained positively for calretinin and inhibin, which is indicative of adrenal cortical carcinoma; the other exhibited strong expression of vimentin and desmin, which was concordant with sarcomatous change and confirmed the diagnosis of adrenal cortical carcinosarcoma. This unique histology with both carcinomatous and sarcomatous components presents a diagnostic challenge for clinicians. As such, adrenal carcinosarcomas should be kept on the differential when evaluating retroperitoneal masses. Additionally, this study includes a review of 34 previously reported cases of adrenal cortical carcinosarcomas along with a discussion about the future exploration of this pathology.